Ageing Well in Digital Times: Trustworthy AI for the Healthcare Sector - Marlene Kulla; Önder Çelik; Justyna Stypińska (WZB-Mitteilungen: Quartalsheft für Sozialforschung, 2025)
Artificial intelligence (AI) is widely regarded as a promising development in the healthcare sector, with anticipated benefits such as improved diagnostic accuracy, earlier detection of health risks, and enhanced support for older adults through assistive technologies. Yet, the development and use of such technologies raises questions about justice, participation, and responsibility.
Keywords: 300